1976
DOI: 10.1021/bi00670a008
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of ribosome-dependent photoinduced chain breakage of the 16S ribosomal ribonucleic acid component of the Escherichia coli 30S ribosomal subunit

Abstract: The effects of 253.7-nm radiation on the structural integrities of free and ribosome-bound 16S ribosomal ribonucleic acid (rRNA) have been elucidated. Exposure of aqueous solutions of Escherichia coli 30S ribosomal subunits to 253.7-nm radiation results in RNA-chain scission and the formation of single-stranded breaks in double-stranded regions of the ribosome-bound 16S rRNA. The minimum doses of incident 253.7-nm radiation required for the first detection of the two types of RNA chain breaks are 2 X 10(20) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Pyrimidine dimer formation results from UV irradiation, and this can lead to locally denatured regions in DNA (21). RNA strand breakage has been reported upon UV irradiation of ribosomes (22,23), and protein chain breakage has been implicated as another side" reaction (24). It is certainly conceivable that, in some cases, such UVinduced damage could perturb the native structure under study and thus result in misleading crosslinking data.…”
Section: Ultraviolet Lightmentioning
confidence: 99%
“…Pyrimidine dimer formation results from UV irradiation, and this can lead to locally denatured regions in DNA (21). RNA strand breakage has been reported upon UV irradiation of ribosomes (22,23), and protein chain breakage has been implicated as another side" reaction (24). It is certainly conceivable that, in some cases, such UVinduced damage could perturb the native structure under study and thus result in misleading crosslinking data.…”
Section: Ultraviolet Lightmentioning
confidence: 99%
“…Gorelic (1975aGorelic ( ,b, 1976aGorelic ( ,b, 1977 has discussed, in detail, this factor and a number of other factors that must be properly evaluated before solid conclusions can be drawn about interactions of particular proteins with rRNA from photochemical cross-linking studies. Furthermore, account must be taken of such additional complexities as the occurrence of RNA and protein chain breakage (Gorelic, 1976c, Gorelic andParker, 1978), amino acid modification, and formation of nonadduct base photoproducts; all of these reactions could cause conformational changes and introduce difficulties in assessing the meaning of photochemical cross-linking experiments in intact ribosomes. It appears that the complete elucidation of the photochemistry of the intact E. coli ribosome and its subunits, over the fluence range of UV radiation required to cross-link most of the ribosomal proteins to rRNA, will be a challenging task.…”
Section: Rna Virusesmentioning
confidence: 99%
“…The difference does not seem to come from chain breakage of RNA which would be counted as solubilized RNA in Gorelic's measurements but may not be precipitable by TCA in our case. In fact, Gorelic showed that chain breakage of RNA is rather limited at the doses he used to obtain complete solubilization of RNA (Gorelic, 1976~). The difference does not appear to be the presence of oxygen in our case (Fig.…”
Section: Inactication Action Spectrummentioning
confidence: 53%
“…Evidence has been presented in a number of laboratories indicating that exposure of solutions of E . coli 30S, 50s and 70s ribosomes to 254nm radiation results in the formation of covalent crosslinks between the rRNA and protein components of the ribosome (Gorelic, 1975a(Gorelic, ,b, 1976aEhresmann et a/., 1975-1976: Moiler and Brimacombe, 1975. The dose dependence of the photocrosslinking reactions has also been investigated in these studies.…”
Section: Introductionmentioning
confidence: 99%